ARPOS: Internet mapping technique for web-based remote supervision of artificial reefs positioning - Man, Mustafa; Mohd Saman, Md Yazid; M. Noor, Noor Maizura; Samo, Khalid; W.A.Bakar, W. Aezwani (2008)
In upcoming years, the strategies for maintenance, traceability, management and operation of productive processes will demand the use of novel information and communication technologies.Supervisory systems in these new scenarios will have to be able to integrate large volumes of information and knowledge coming both from local and remote points of large processors. In the fisheries industry, Artificial Reefs is one of the most important devices for the conservation and sustainability of fish and their biodiversity to make sure that the species will sustain and retain.In this work, the authors present an internet mapping technique for web-based remote supervision of artificial reefs positioning that incorporates powerful data and knowledge visualization too ls based on map.This architecture adds an intermediate layer (database) to well- known client and server layers that isolates the client part from the committee of the fishery bodies involved in storing data for artificial reefs positioning, and accessed and visualized it through on-line application.